The Stress Barometer: Validation of a Bio–Psycho–Social Brief Screening Instrument of Pandemic Stress Reaction - Eckhard, Alina; Menne, Britta; Salzburger, Mareike; Poppelreuter, Martin; Bering, Robert (Frontiers in Psychology, 2022)
Background To capture the psychosocial impact of the SARS-CoV-2 pandemic, a model based on the International Classification of Functioning, Disability, and Health (ICF) was developed during the first lockdown in Germany in April 2020. FACT-19, the questionnaire for the assessment of pandemic stress load, measures (1) pre-pandemic stress, (2) pandemic stress, and (3) contextual factors (functioning as facilitators or barriers). Derived from this model, the stress barometer as a brief screening instrument captures these factors. The purpose of this study is a preliminary validation of the instrument. Method The stress barometer was applied in conjunction with the Symptom-Checklist SCL-90-S at the beginning of the first lockdown in psychosomatic and psychotraumatological care in two federal states in Germany. The sample consists of n = 341 (68.6% female) from 18–73 years of age (M = 49.36, SD = 11.4). Results The structure of the short screening was examined in the overall sample using an exploratory factor analysis [Chi2 (78) = 875.720, KMO = 0.688]. The results indicate a four-factor-structure that explains 59.5% of the total cumulative variance. The factors of the stress barometer correlate with the Global Severity Index (GSI, measured by SCL-90-S) with moderate to weak effects: pre-pandemic stress (rs = 0.431, p < 0.001, n = 295), pandemic stress (rs = 0.310, p < 0.001, n = 298), distal facilitator (rs = −0.155, p < 0.001, n = 312), and proximal barriers (rs = 0.232, p < 0.001, n = 312). Discussion The results indicate the suitability of the stress barometer to complement the measurement of the impact of pandemics with an ICF-oriented approach, taking into consideration pre-pandemic stress as well as interactions with facilitators and barriers. Further analysis will be necessary for a revision of the items of the scale.